2022
DOI: 10.47657/5880
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Q Index Ranked Journals: Library and Information Science Productivity and Research Trends (2011-2020)

Abstract: Publishing in the prestigious research avenues is considerable important for the researchers and academicians. However, selecting the right journal to suit the research topic and quality of research is a tiresome task. Studying the nature of the research published in differently ranked journals is important to understand the difference of research and publication trends. This study aims to examine a differences and similarities of the research published in the Q1 and Q4 ranked Library and Information Science (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…He explored that Pakistan had 201 (77%) OA journals and DOAJ (2022) had registered 94 OA journals originating from Pakistan. Qutab (2012) identified that Pakistan had 135 full-text OA journals. However, my study explored 297 (90%) OA scholarly journals in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He explored that Pakistan had 201 (77%) OA journals and DOAJ (2022) had registered 94 OA journals originating from Pakistan. Qutab (2012) identified that Pakistan had 135 full-text OA journals. However, my study explored 297 (90%) OA scholarly journals in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…The reviewed literature confirmed that there have been several studies carried out worldwide on the status of OA scholarly journal publishing. From a Pakistani perspective, a few studies on a smaller scale (Qutab, 2012;Sheikh, 2017Sheikh, , 2020 were conducted. Hence, there was a potential gap in the existing literature which motivated the researcher to explore the current status of OA scholarly journal publishing in Pakistan.…”
Section: Oa Publishing In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology has undoubtedly impacted every sphere of life (Al Qalhati et al, 2020; Murphy and Newport, 2021; Tabatabaei and Gui, 2011), and libraries are no exception (Bayani et al, 2017; Merkulova, 2021; Qutab et al, 2014; Ramzan et al, 2021). Libraries of today are more technology-oriented than ever before regarding their resources, operations, services, and physical spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The technology savvy library users hold high expectations from the libraries comparing with other information and technology provider competitors. Consequently, libraries must continually explore new technologies to cater to the emerging needs of their users and to ensure continuation of efficient operations and services (Goswami and Pandya, 2019; Onuoha et al, 2019; Qutab et al, 2014; Seal, 2015). However, libraries are challenged by limitation of financial share and access to resources that eventually may impact the library operations and services.…”
Section: Introductionmentioning
confidence: 99%